ANALYSIS OF FACTORS THAT INFLUENCE LEFTOVERS IN HOSPITAL PATIENTS AT SECOND HOSPITAL dr. SOEPRAOEN MALANG - Wiyasti, Eri; Nurwijayanti; Setyo Budi Susanto (Universitas STRADA Indonesia, 2019)
Leftovers are one simple indicator that can be used to evaluate the success of hospital nutrition services. The presence of food residues for hospitalized patients can be caused by internal factors and external factors. Internal factors include the appearance of food when served, the taste of food when eaten and a variety of menus. External factors include stress, appetite, type of illness, likes or dislikes, the presence of dietary restrictions and eating habits. The general objective of this study was to analyze the factors that influence the remaining food of patients in the inpatient room of the Second Hospital of dr. Soepraoen Malang. This study was an observational research that was descriptive analytic, the data collection was done by cross sectional method with instantaneous variable measurements with the help of instruments in the form of questionnaires and direct observation. The sampling technique uses purposive sampling technique. The independent variable is the taste of the menu which includes the appearance and taste of food, the dependent variable is leftovers. Data retrieval was carried out on 30 respondents, then all data were analyzed using statistical tests. Respondents who stated their appearance at Second Hospital dr. Soepraoen Malang with interesting categories as much as 80.0% and enough categories as much as 20.0%. Respondents stated that the taste of food with interesting categories was 46.6% and enough categories as much as 53.4%. The menu of rice and vegetables is left 50-75%, the menu of animal side dishes, vegetable dishes and fruit is left 25-50%. Linear regression test showed that there was an effect of appearance on leftovers (p = 0.032), there was an effect of taste on leftovers (p = 0,000) and there was an influence on appearance and taste on leftovers (p = 0,000).